Aspek Keadilan Pancasila dalam Mediasi Perselisihan Hubungan Industrial Pada Dinas Perindustrian Dan Tenaga Kerja Kabupaten Sukoharjo - Fajar, Sukmajati; Subekti, Rahayu (Jurnal Komunikasi Hukum (JKH), 2021)
The purpose of writing this research is to find out about pancasila justice in the of industrial relations dispute mediation at the Departement of Industry and Manpower of Sukoharjo Regency. The writing of this research uses a normative juridicial legal research method by reviewing library materials or secondary data. The nature of the data research and the approach used are prescriptive and statute approach. Pancasila Justice has characteristic of humanizing humans in a fair and civilized manner according to their human rights and providing social justice for all Indonesian people. From the data dispute cases that have been analyzed, there are still procedures and recommendations that are not in accordance with Law Number 2 of 2004 concerning Settlement of Indutrial Relations Disputes, Law Number 13 of 2003 concerning Manpower and Pancasila Justice. This legal fact causes dispute resolution through mediation to be unfair because it is not in accordance with Pancasila justice where Pancasila jutice has the characteristics of humanizing humans fairly and civilly according to their human rights and providing social justice for all Indonesian people.